Sintesa Islam-Jawa dalam Sěrat Wulang Dalěm Pakubuwana II - Dwiadmojo, Ghis Nggar; Kurniawan, Abimardha; Mulyani, Hesti; Ekowati, Venny Indria; Gunawan, Eko; Dewi, Yusi Nurcahya (YASIN, 2025)
This study aims to examine the synthesis of Islamic and Javanese elements in the Serat Wulang Dalem Pakubuwana II (SWDPB II), as found in manuscript Ms. Orient Okt 1224 from the Staatsbibliothek Berlin collection. The research adopts a new historicism approach, which views literary works as inseparable from the historical, social, political, and economic contexts of their time. The data consist of textual excerpts from the manuscript, analyzed to identify manifestations of Islamic-Javanese cultural synthesis. The findings reveal that this synthesis is articulated through the use of terminology drawn from two distinct traditions that are harmoniously juxtaposed, such as Arabic and Javanese scripts, the figures of prophets and kings, and the symbolic pairing of the right and left eyes. Within the textual construction, these elements are interpreted as complementary rather than oppositional. This synthesis reflects an intellectual and spiritual response to the evolving ethical and social dynamics of the 19th century, particularly in the context of the interaction between Islam and Javanese culture within the royal court.